A silicon-carbon composite material containing nano silicon-based film and preparation method thereof
By using plasma-enhanced chemical vapor deposition method to generate nano-silicon-based thin films in the negative electrode material of lithium-ion battery, the problem of volume expansion and uneven dispersion of silicon materials is solved, and the circulation performance and first-week efficiency of lithium-ion batteries are improved. A higher energy density is achieved.
Patent Information
- Application Number
- CN202211647431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing lithium-ion battery negative electrode material silicon has poor circulation performance due to its large volume expansion and shrinkage rate and low electronic conductivity. In addition, the nano-silicon carbon composite materials are difficult to disperse evenly during the preparation process, resulting in poor circulation performance.
The vapor deposition method of plasma enhanced chemistry is used to generate nano-silicon-based films on the surface of the molten carbon source, and it is evenly dispersed by scraping the coating with scraper. Combined with high-temperature carbonization treatment, silicon-carbon composite materials containing nano-silicon-based films are formed to reduce the volume expansion effect. and uneven stresses to improve cycling performance.
By generating a small-size, uniformly dispersed nano-silicon-based film, the circulation performance and first-week efficiency of the negative electrode material of lithium-ion battery are significantly improved, the consumption of active lithium is reduced, the number of negative electrode cracks is reduced, and the stability of the material is improved.
Smart Images

Figure CN115832259B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to a silicon-carbon composite material containing a nano silicon-based film and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of long cycle life, high operating voltage, high specific energy, and low self-discharge, and are therefore widely used in electronic products, portable power tools, and electric vehicles. With the rapid development of electronic technology and the growing market for new energy vehicles, the market demand for lithium-ion batteries with higher energy density is becoming more urgent. However, the negative electrode used in commercial lithium-ion batteries is a graphite negative electrode, and its theoretical specific capacity is only 372mAh / g, which cannot meet the requirements of high energy density batteries. Therefore, people are eager to find a negative electrode material with a high specific capacity that can replace graphite. Among them, silicon is considered to be an ideal choice for the next generation of lithium-ion battery negative electrode materials due to its relatively high specific capacity (4200mAh / g) and low lithium desorption platform.
[0003] However, the volume expansion and contraction rate of silicon anode during lithium insertion and extraction is greater than 300%, which makes its cycle performance in lithium batteries poor; in addition, silicon has low electronic conductivity and ionic conductivity, which makes its rate performance poor. At present, in order to improve the above problems, people combine silicon materials with carbon substrates.
[0004] Traditional nano-silicon-carbon composite materials are obtained by mechanically grinding silicon into nano-silicon, then dispersing the nano-silicon in a carbon source, and finally carbonizing to obtain a silicon-carbon composite material. However, the nano-silicon in this method is difficult to be evenly dispersed in the carbon source. Secondly, it is also difficult to grind silicon to a size below 50nm by mechanical grinding, resulting in poor cycle performance of the silicon-carbon composite material obtained by this method. Patent CN107507972B pickles silicon alloy powder to obtain porous silicon, then carbonizes it, and finally carbonizes it to obtain a silicon-carbon composite material. Although the porous structure of porous silicon in this method alleviates the expansion problem of silicon during lithium insertion and extraction to a certain extent, the size of the porous silicon itself is relatively small. The large size leads to its poor cycle performance; in patent CN115020689B, the pore walls and outer surfaces of porous carbon microspheres containing through holes are first covered with a coating containing transition elements, and then silane is decomposed to deposit silicon particles inside the pores and on the outer surface to obtain a nano-silicon-carbon composite material. This method is a relatively promising method on the market, but the silicon decomposed by silane in this method is deposited from the outside to the inside. This deposition can easily fill the pores on the surface, leaving less silicon deposited in the pores inside the particles. Secondly, the utilization rate of silane decomposition and deposition inside the porous carbon particles is low, and most of it is decomposed before reaching the surface of the particles. The effect of the prepared silicon-carbon composite material is not ideal. Summary of the invention
[0005] The object of the present invention is to provide a silicon-carbon composite material containing a nano silicon-based film and a preparation method thereof. The silicon-carbon composite material contains a nano silicon-based film with a small size, uniform dispersion and small specific surface area, which effectively reduces the number of cracks in the negative electrode and has high stability, so that it consumes less active lithium during the first lithium insertion process and has a higher first-week efficiency.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A silicon-carbon composite material containing a nano-silicon-based film, comprising a plurality of silicon-carbon particles, wherein the silicon-carbon particles include a carbon substrate, a nano-silicon-based film embedded in the carbon substrate, and a carbon coating layer on the surface of the silicon-carbon particles;
[0008] The thickness of the nano silicon-based film is 0.1-50nm, and the median area of the nano silicon-based film is greater than 10nm 2 ;
[0009] The carbon coating layer has a thickness of 1 nm-1 um.
[0010] Furthermore, the nano-silicon-based film is an irregularly shaped sheet structure.
[0011] Furthermore, the nano silicon-based film is at least one of a single silicon material and a silicon alloy material.
[0012] Furthermore, the carbon substrate is one or more of hard carbon and soft carbon, or a composite of the carbon substrate and one or more of graphite, carbon nanotubes, carbon fibers and graphene.
[0013] Furthermore, the mass ratio of silicon in the silicon-carbon composite material is 0.1%-70%, and the particle size of the silicon-carbon composite material is 3-30 um;
[0014] A method for preparing the silicon-carbon composite material containing a nano-silicon-based film comprises the following steps:
[0015] S1. Place a solid carbon source with a softening point of 80-400°C into a heating chamber at a temperature of 80-400°C, evacuate to maintain a vacuum degree of 0.1Pa-1000Pa, heat the solid carbon source to a molten state, drop the molten solid carbon source onto a rotating disc substrate at a temperature of 150-400°C, use a scraper to spread and flatten it, then introduce silicon source gas to crack the silicon source by plasma enhanced chemical vapor deposition, and deposit it on the surface of the molten carbon source to form a nano silicon-based film, and make the generated nano silicon-based film uniformly dispersed in the molten carbon source by continuous scraping and flattening and silicon deposition to obtain a precursor of a silicon-carbon composite material;
[0016] S2. After the reaction in step S1 is completed, the silicon source gas is turned off, and after natural cooling, the rotating disk substrate loaded with the silicon-carbon composite material precursor and the silicon-carbon composite material precursor are transferred to a vacuum or inert gas atmosphere furnace for high-temperature carbonization to form a silicon-carbon composite material. The carbonization treatment temperature is 900 to 1200°C, the carbonization treatment time is 1 to 6 hours, and the heating rate of the carbonization treatment is 0.5 to 20°C / min;
[0017] S3. After the carbonization in step S2 is completed and cooled to room temperature, the silicon-carbon composite material is crushed and classified to obtain a silicon-carbon composite negative electrode material containing a nano-silicon-based film.
[0018] Furthermore, in step S1, the silicon source gas composition is silane and a diluent gas, or at least one of silicon tetrachloride, dichlorosilane, trichlorosilane and a diluent gas; the solid carbon source is selected from one or a combination of at least two of isotropic coal tar pitch, isotropic petroleum asphalt, mesophase asphalt or polymer materials, or a composite thereof with one or more of graphite, carbon nanotubes, carbon fibers and graphene.
[0019] Furthermore, in the step S1, a non-metallic element gas source may be introduced at the same time as the silicon source gas is introduced, so that the nano-silicon-based film contains silicon alloy material.
[0020] Furthermore, the silicon-carbon composite negative electrode material obtained in step S3 may be carbon-coated by chemical vapor deposition or pyrolysis to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.
[0021] Furthermore, the silicon-carbon composite material is applied to the negative electrode of a lithium-ion battery.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] 1. The thickness of the nano silicon-based film is small. The present invention can generate a nano silicon-based film with a thickness of 0.1nm-50nm by using a plasma enhanced vapor deposition method. The small-sized nano silicon-based film can effectively alleviate the volume expansion effect of the silicon-carbon composite material in the negative electrode, thereby improving the cycle performance of the material;
[0024] 2. Silicon is evenly dispersed. Different from the method of dispersing nano-silicon particles in a carbon source and then carbonizing them, the present invention performs production and dispersion simultaneously, generates a nano-silicon-based film on the surface of a molten carbon source, and evenly disperses the nano-silicon-based film in the carbon source by extruding and flattening the nano-silicon-based film and the molten carbon source. Therefore, the nano-silicon-based film in the silicon-carbon composite material obtained after carbonization of the precursor is also evenly dispersed;
[0025] 3. The overall expansion stress is uniform, the nano-silicon-based film has small dispersed particles and is evenly dispersed, which reduces the cracking of the silicon-carbon composite negative electrode due to uneven stress during the cycle process;
[0026] 4. Small silicon specific surface area. The nano-silicon-based film obtained by the plasma-enhanced vapor deposition method of the present invention has a smaller specific surface area than zero-dimensional nano-silicon particles and one-dimensional nano-silicon wires of the same particle size, so that less active lithium is consumed in the formation of SEI film during the first lithium insertion process, making the silicon-carbon composite material of the present invention have a higher first-cycle efficiency than the negative electrode materials of the same specific capacity of other patents. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Attached Figure 1 It is a structural schematic diagram of the present invention.
[0028] Attached Figure 2 This is the first cycle charge and discharge curve of Example 1 of the present invention.
[0029] Attached Figure 3 It is a 50-week capacity retention rate graph of Example 1 of the present invention and Comparative Example 1.
[0030] Numbers shown in the accompanying drawings:
[0031] 1. Carbon coating layer; 2. Carbon substrate; 3. Nano-silicon-based film; 4. Cross section of nano-silicon-based film. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the application equally.
[0033] Embodiment 1: A silicon-carbon composite material containing a nano-silicon-based film, comprising a nano-silicon-based film uniformly embedded in a carbon substrate of hard carbon and a carbon coating layer on the surface of silicon-carbon particles; the nano-silicon-based film is an irregularly shaped sheet structure, wherein the mass ratio of silicon in the silicon-carbon composite material is 40.7%, and the particle size of the silicon-carbon composite material is 21um; the thickness of the nano-silicon-based film is 30.7nm, and the median area of the nano-silicon-based film is 180nm 2 ; The thickness of the carbon coating layer is 10.5nm.
[0034] A method for preparing a silicon-carbon composite material containing a nano-silicon-based film comprises the following steps:
[0035] S1. Put petroleum asphalt with a softening point of 120°C into a heating chamber with a temperature of 250°C, evacuate and maintain a vacuum degree of 180Pa, and heat the petroleum asphalt to a molten state, adjust the rotation speed of the rotating disk substrate to 100rpm, and drip the molten petroleum asphalt onto the rotating disk substrate with a temperature of 270°C. The temperature of the rotating disk substrate should be higher than the softening point of the petroleum asphalt. Adjust the distance between the scraper and the disk to 5um, and use the scraper to spread and flatten. After the nano-silicon-based film is deposited on the surface of the molten petroleum asphalt, it is spread by the scraper to form an effect similar to extrusion dispersion. Through continuous scraping, the nano-silicon-based film can be evenly dispersed in the silicon source, and then silane is introduced at a flow rate of 35sccm and hydrogen is introduced at a flow rate of 4sccm. , the silicon source is cracked by plasma enhanced chemical vapor deposition method, the equipment selected for plasma enhanced chemical vapor deposition method is VHFCVD, the radio frequency power of the equipment is turned on, the radio frequency power is adjusted to 15w, and it is deposited on the surface of molten petroleum asphalt, and the silane gas undergoes plasma glow discharge phenomenon and is deposited on the squeezed and flattened molten petroleum asphalt surface to form a nano silicon-based film, and the deposition is 3h. In this process, the nano silicon-based film deposited on the surface of the petroleum asphalt is continuously flattened by a scraper and silicon is deposited so that the generated nano silicon-based film is evenly dispersed in the molten petroleum asphalt, and the precursor of the silicon-carbon composite material is obtained; it should be noted that, under the premise that other conditions remain unchanged, the thickness of the nano silicon-based film has a certain positive correlation with the silane gas flow rate and the rotation speed of the rotating disk;
[0036] S2. After the reaction in step S1 is completed, the silicon source gas is turned off, the heating is stopped, and after natural cooling, the rotating disk substrate loaded with the silicon-carbon composite material precursor and the silicon-carbon composite material precursor are transferred to a box-type atmosphere furnace together, and the temperature is raised to 900° C. at 2° C. / min under the protection of inert gas nitrogen for carbonization for 4 hours, and then the temperature is lowered to room temperature to obtain a bulk silicon-carbon composite material;
[0037] S3. After the carbonization in step S2 is completed, the mixture is cooled to room temperature, and the obtained blocky silicon-carbon composite material is crushed by a jet mill and classified to obtain D 50 = A silicon-carbon composite negative electrode material containing a nano-silicon-based film with a particle size of 19.6 μm. The silicon-carbon composite material of the present invention is used for the production and preparation of lithium-ion batteries.
[0038] The silicon-carbon composite negative electrode material obtained in step S3 may also be carbon-coated by chemical vapor deposition or pyrolysis to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.
[0039] Carbon coating by chemical vapor deposition: The powdered silicon-carbon composite material obtained in step S3 is placed in an intermittent CVD furnace, methane and nitrogen are introduced, the temperature is raised to 800°C at 5°C / min, and after keeping the temperature for 5 hours, the silicon-carbon composite material with a carbon coating layer is obtained after natural cooling.
[0040] Embodiment 2: A silicon-carbon composite material containing a nano-silicon-based film, comprising a nano-silicon-based film uniformly embedded in a composite carbon substrate composed of soft carbon and carbon fiber and a carbon coating layer on the surface of silicon-carbon particles, wherein the nano-silicon-based film is an irregularly shaped sheet structure, wherein the mass ratio of silicon in the silicon-carbon composite material is 51.6%, and the particle size of the silicon-carbon composite material is 12.7um; the thickness of the nano-silicon-based film is 35.6nm, and the median area of the nano-silicon-based film is 305nm 2 ; The thickness of the carbon coating layer is 20.5nm.
[0041] It is prepared by the preparation method in Example 1, wherein various parameters such as temperature, material selection, equipment, etc. can be selected and adjusted within the scope described in the present invention.
[0042] Embodiment 3: A silicon-carbon composite material containing a nano-silicon-based film, comprising a nano-silicon-based film uniformly embedded in a soft carbon carbon substrate and a carbon coating layer on the surface of silicon-carbon particles, wherein the nano-silicon-based film is an irregularly shaped sheet structure, wherein the mass ratio of silicon in the silicon-carbon composite material is 69.8%, and the particle size of the silicon-carbon composite material is 7.9um; the thickness of the nano-silicon-based film is 6.1nm, and the median area of the nano-silicon-based film is 100nm 2 ; The thickness of the carbon coating layer is 30.5nm.
[0043] It is prepared by the preparation method in Example 1, wherein various parameters such as temperature, material selection, equipment, etc. can be selected and adjusted within the scope described in the present invention.
[0044] Embodiment 4: A silicon-carbon composite material containing a nano-silicon-based film, comprising a phosphorus-doped nano-silicon-based film uniformly embedded in a composite carbon substrate composed of hard carbon and graphite, and a carbon coating layer on the surface of silicon-carbon particles, wherein the nano-silicon-based film is an irregularly shaped sheet structure, wherein the mass ratio of silicon in the silicon-carbon composite material is 30.4%, the mass ratio of phosphorus is 1.1%, and the particle size of the silicon-carbon composite material is 10.8um; the thickness of the nano-silicon-based film is 15.1nm, and the median area of the nano-silicon-based film is 128nm 2 ; The thickness of the carbon coating layer is 10.2nm.
[0045] It is prepared by the preparation method in Example 1, wherein various parameters such as temperature, material selection, equipment, etc. can be selected and adjusted within the scope described in the present invention.
[0046] Comparative Example 1: 50 nm nano-silicon was prepared by sand milling, and then the nano-silicon and asphalt were dispersed and dissolved in n-hexane. After spray drying, the mixture was heated to 1150°C at 2°C / min under the protection of inert gas nitrogen and carbonized for 4 h. The mixture was then cooled to room temperature to obtain a bulk silicon-carbon composite material. The composite material was crushed by a jet mill and classified to obtain D 50 = 8um particle size silicon-carbon composite negative electrode material containing nano-silicon; put it into an intermittent CVD furnace, introduce methane and nitrogen, heat it to 800℃ at 5℃ / min, keep it warm for 5h, and then cool it naturally to obtain a silicon-carbon composite material with a 10um thick carbon coating layer. The mass content of silicon in the material is 41.2%.
[0047] Electrochemical testing:
[0048] (1) The silicon-carbon composite material particles, SP and LA133 (Indile) prepared in the above examples and comparative examples were used to prepare a slurry in a mass ratio of 70:20:10, coated on an 8 μm copper foil, and dried in a forced air oven at 70°C for 2 h. Then, several electrodes with a diameter of 12 mm were cut and assembled in a vacuum oven at 110°C for 7 h.
[0049] (2) After baking, the cells were quickly transferred to a glove box, and a 14 mm Φ lithium metal sheet was used as the counter electrode. A double-sided ceramic diaphragm was used, and 1 mol / L LiPF6 / (EC+DMC) (volume ratio 1:1) plus 3% VC and 3% FEC was used as the electrolyte. The button cell was assembled in the gloves, and the water and oxygen content in the glove box was controlled below 0.1 ppm.
[0050] (3) The assembled battery was subjected to charge and discharge cycle test. The test equipment was charged and discharged. The test was conducted on the LAND battery test system (from Wuhan Lanhe Electronics Co., Ltd.). The test conditions were: room temperature, 0.1C and 0.02C step discharge to 5 mV in the first two weeks, 0.1C constant current charging to 1.5 V, and 0.1C / 0.1C charge and discharge cycle for 50 weeks after the second week.
[0051] The results are shown in Table 1 (the calculation method of material charge capacity is: charge capacity / negative electrode active material mass; battery 50-week capacity retention rate: charge capacity of the 50th week / charge capacity of the first week)
[0052] Table 1 Performance test results of silicon-carbon composite material particles of Examples 1-4 and Comparative Example 1
[0053]
[0054] According to Examples 1-4 in Table 1, it can be found that the first efficiency and cycle retention rate of the silicon-carbon negative electrode material prepared by the present invention are relatively high. This is because the silicon material in the silicon-carbon negative electrode material of the present invention exists in the form of a nano-silicon film, which makes it smaller than the zero-dimensional nano-silicon particles and one-dimensional nano-silicon wires of the same particle size. The specific surface area is smaller, so that less active lithium is consumed in the generation of the SEI film during the first lithium insertion process, so the first-week efficiency will be relatively high; secondly, since the silicon material in the silicon-carbon negative electrode material has a small particle size and exists in the form of a thin film, the small particles of silicon have less effect on the overall expansion during the cycle, and the nano-silicon-based thin film has small dispersed particles and is evenly dispersed, which reduces the rupture of the silicon-carbon composite negative electrode due to uneven stress during the cycle, thereby making the cycle retention rate higher.
[0055] According to the data of Example 1 and Comparative Example 1 in Table 1, although the content of silicon in Example 1 and Comparative Example 1 is roughly the same, the first-week charging capacity and first-week efficiency of Comparative Example 1 are not as good as those of Example 1. Figure 2 From the 50-week cycle capacity retention rate graph of Example 1 and Comparative Example 1, it is obvious that the capacity retention rate of Comparative Example 1 decreases faster, indicating that its cycle performance is worse than that of Example 1. This is because the nano-silicon particles in Comparative Example 1 are first dispersed in the carbon source and then carbonized, which will lead to uneven dispersion, and some of them may agglomerate together, making it difficult to fully utilize their capacity; on the other hand, the 50nm nano-silicon particles themselves have a larger specific surface area than the film composed of 50nm nano-silicon, so more active lithium is consumed in the formation of SEI film during the first lithium insertion process, resulting in a lower first efficiency of Comparative Example 1; finally, the nano-silicon in Comparative Example 1 is difficult to disperse evenly, so the stress of silicon expansion of the silicon-carbon material in Comparative Example 1 during the cycle will be uneven, which will cause the material to rupture, resulting in poor cycle performance.
Claims
1. A method for preparing a silicon-carbon composite material containing a nano-silicon-based film, characterized in that: The method comprises a plurality of silicon-carbon particles, wherein the silicon-carbon particles comprise a carbon substrate, a nano-silicon-based film embedded in the carbon substrate, and a carbon coating layer on the surface of the silicon-carbon particles; The thickness of the nano silicon-based film is 0.1-50nm, and the median area of the nano silicon-based film is greater than 10nm 2 ; The carbon coating layer has a thickness of 1 nm to 1 um; The following steps are also included: S1. Place a solid carbon source with a softening point of 80-400°C into a heating chamber at a temperature of 80-400°C, evacuate to maintain a vacuum degree of 0.1Pa-1000Pa, heat the solid carbon source to a molten state, drop the molten solid carbon source onto a rotating disc substrate at a temperature of 150-400°C, use a scraper to spread and flatten it, then introduce silicon source gas to crack the silicon source by plasma enhanced chemical vapor deposition, and deposit it on the surface of the molten carbon source to form a nano silicon-based film, and make the generated nano silicon-based film uniformly dispersed in the molten carbon source by continuous scraping and flattening and silicon deposition to obtain a precursor of a silicon-carbon composite material; S2. After the reaction in step S1 is completed, the silicon source gas is turned off, and after natural cooling, the rotating disk substrate loaded with the silicon-carbon composite material precursor and the silicon-carbon composite material precursor are transferred to a vacuum or inert gas atmosphere furnace for high-temperature carbonization to form a silicon-carbon composite material. The carbonization treatment temperature is 900 to 1200°C, the carbonization treatment time is 1 to 6 hours, and the heating rate of the carbonization treatment is 0.5 to 20°C / min; S3. After the carbonization in step S2 is completed and cooled to room temperature, the silicon-carbon composite material is crushed and classified to obtain a silicon-carbon composite negative electrode material containing a nano-silicon-based film.
2. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: The nano silicon-based film is an irregularly shaped sheet structure.
3. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: The nano silicon-based film is at least one of a single silicon material and a silicon alloy material.
4. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: The carbon substrate is one or more of hard carbon and soft carbon, or a composite of the carbon substrate and one or more of graphite, carbon nanotubes, carbon fibers and graphene.
5. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: The mass ratio of silicon in the silicon-carbon composite material is 0.1%-70%, and the particle size of the silicon-carbon composite material is 3-30 um.
6. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: In the step S1, the silicon source gas composition is silane and a diluent gas, or at least one of silicon tetrachloride, dichlorosilane, trichlorosilane and a diluent gas; the solid carbon source is selected from one or a combination of at least two of isotropic coal tar pitch, isotropic petroleum asphalt, mesophase asphalt or polymer materials, or a composite thereof with one or more of graphite, carbon nanotubes, carbon fibers and graphene.
7. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: In the step S1, a non-metallic element gas source can be introduced at the same time as the silicon source gas is introduced, so that the nano-silicon-based film contains silicon alloy material.
8. The method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to claim 1, characterized in that: The silicon-carbon composite negative electrode material obtained in step S3 can also be carbon-coated by chemical vapor deposition or pyrolysis to obtain a silicon-carbon composite negative electrode material containing a carbon coating layer.
9. A method for preparing a silicon-carbon composite material containing a nano-silicon-based film according to any one of claims 1 to 8, characterized in that: The silicon-carbon composite material is applied to the negative electrode of a lithium-ion battery.
Citation Information
Patent Citations
Preparation methods of silicon-carbon anode materials, silicon-carbon anode materials and lithium-ion batteries
CN107507972B
Nano-silicon-carbon composite materials for secondary lithium batteries, their preparation methods and applications
CN115020689B
Carbon / silicon / carbon nano composite structure cathode material and preparation method thereof
CN102214817A
Silicon-carbon composite negative electrode material for lithium ion battery and preparation method thereof
CN103474667A
Carbon-coated nano silicon / graphene / cracked carbon layer composition material, preparation method, and lithium ion battery including the composition material
CN106067547A
